Assessment of Mental Workload and its Association with Workability among Nurses Working in the Care Units of Patients with Covid-19 - Seyvan Sobhani; Sara Tabanfar; Isa Mohammadi Zeidi; Mohammad Sharif Hosseini (Shiraz University of Medical Sciences, 2023)
Background: High mental workload can negatively affect nurses' mental and physical health, quality of life, and workability. Therefore, the present study aimed to determine the relationship between mental workload and the workability among nurses.Methods: Using the multi-stage sampling method, the researchers selected 142 nurses working in Qazvin hospitals in Covid-19 patient care units to participate in a cross-sectional descriptive study. Data collection tools included a demographic information questionnaire, the NASA Workload Index, and Workability Index. Data were analyzed by independent t-test, Pearson correlation coefficient, and ANOVA in SPSS software.Results: The mean age of participants was 31.3±6.1 years, and the work experience mean was 7.6±5.8 years. The results showed a high mental workload (80.4±13.4) and moderate workability (31.8±7.3). The number of nurses' shifts per month was negatively correlated with workability (P=0.032). ICU nurses had the highest mental workload score and the lowest workability score. Also, workability there was a significant negative correlation between mental workability and workload (r=-0.579 & P<0.001).Conclusion: A reverse correlation was observed between mental workload and workability. To improve the performance and mental health of nurses, frequent training programs and management interventions should be practiced.